Biodiversity and Investigating Pathogenic Levels of Endogenous Strains of Pandora neaoaphidis Collected from Cruciferous Crops in Northern Thailand - Kawpet, R.; De Bels, M.; Saengyot, S. (International Journal of Agricultural Technology, 2018)
The biodiversity and virulence of aphid pathogen: Pandora (Erynia) neoaphidis from cruciferous crops covering thirteen districts in Chiang Mai, Lamphun and Lampang provinces, Northern of Thailand were evaluated. Base on phenotypic level, 128 isolates of P. neoaphidis were collected from various survey location. The result showed that natural occurrence pathogenicity rate of P. neoaphidis was in the range of 11 to 93.13% with an average of 41.22%±12.63. Three isolates (2.3%) showed pathogenic activity higher than 90% including Eyn13 was the most activity of 93.14±4.54 % followed by those of Eyn12 and Eyn14 which had the action of 91.68±5.13 % and 90.30%±23.57, respectively.In addition, these of Eyn04, Eyn17, Eyn16, Eyn20, Eyn15, Eyn24, Eyn02, Eyn18 and Eyn01 showed the natural pathogenic action in the range of 85.89±13.07 to 73.42±9.72, respectively. Contrary, pathogenicity rate of four isolates of P. neoaphidis (Eyn59, Eyn85, Eyn110 and Eyn62) were very low less than 15% which Eyn62 was the lowest (11.13%±5.94). As a whole, 39 isolates of P. neoaphidis established aphid pathogenic traits at 21 to 30% followed by those of 22 isolates at 31-40%, whereas the innate of 52 isolates had pathogenicity in the range of 40 to 100%, respectively.